SALT-MAKING AS A STUNTING ENTERPRISE AND PRACTICE: THE CASE OF ILOCOS SUR, PHILIPPINES - Annabelle B. Francisco; Noel L. Llamar; Ephraine Hyacinth R. Chavez (Universitas PGRI Madiun, 2022)
To document the current circumstances of the salt farmers in Ilocos Sur, Philippines and to confirm if in this side of the country, salt-making is really a ‘dying’ industry, the study used the multiphase case study design. The continuing situation of salt production in the context of the two communities covered in this study, as a low productivity, low-income industry characterized by the presence of a growing intergenerational gap in the transfer of knowledge, skill, and practice in salt making indicates an impending total weakening, if not dying, of the industry in the coming years. Its existence for years without expanding despite its potentiality in sustaining the financial and socio-economic needs of the salt-makers signifies its stunting status, obviously needing an immense recalibration both in the salt makers’ and the government’s mindset of development, process, and technological use.